1998
DOI: 10.1542/peds.101.2.276
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Screening of the BTK Gene in 56 Families With X-Linked Agammaglobulinemia (XLA): 47 Unique Mutations Without Correlation to Clinical Course

Abstract: Our results demonstrate that molecular genetic testing by SSCP analysis provides an accurate tool for the definitive diagnosis of XLA and the discrimination of borderline cases, such as certain hypogammaglobulinemia or common variable immunodeficiency patients with overlapping clinical features. Genotype/ phenotype correlations are not currently possible, making prediction of the clinical course based on molecular genetic data infeasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 34 publications
4
83
0
2
Order By: Relevance
“…6). From in vitro kinase assays of BTK mutants derived from BTK-deficient X-linked agammaglobulinemia patients, it is known that truncation of the BTK kinase domain at amino acid 520 and even replacement mutations in the distal portion of the kinase domain result in a complete loss of BTK kinase activity (4). Hence, only full-length BTK but none of the truncated BTK splice variants identified here should exhibit BTK kinase activity (Table 1, Fig.…”
Section: Rare Occurrence Of Somatic Mutations Of the Btk Gene In B Cellmentioning
confidence: 89%
See 2 more Smart Citations
“…6). From in vitro kinase assays of BTK mutants derived from BTK-deficient X-linked agammaglobulinemia patients, it is known that truncation of the BTK kinase domain at amino acid 520 and even replacement mutations in the distal portion of the kinase domain result in a complete loss of BTK kinase activity (4). Hence, only full-length BTK but none of the truncated BTK splice variants identified here should exhibit BTK kinase activity (Table 1, Fig.…”
Section: Rare Occurrence Of Somatic Mutations Of the Btk Gene In B Cellmentioning
confidence: 89%
“…BTK kinase deficiency in humans leading to X-linked agammaglobulinemia results in a breakdown of pre-B cell receptor signals and a differentiation block at the pre-B cell stage (4). In normal pre-B cells, engagement of the pre-B cell receptor using a -chainspecific antibody (arrows, Fig.…”
Section: Expression Of Kinase-deficient Btk Prevents Pre-b Cell Recepmentioning
confidence: 99%
See 1 more Smart Citation
“…We have predicted the consequences of all the mutations on protein structure and function based on sequence and structure information [Holinski-Feder et al, 1998;Jin et al, 1995;Korpi et al, 2000;Maniar et al, 1995;Mattsson et al, 2000;Okoh and Vihinen, 1999;Saha et al, 1997;Shen and Vihinen, 2004;Speletas et al, 2001;Vihinen et al, 1995aVihinen et al, ,b, 1994aVoøchovský et al, 1995;Zhu et al, 1994]. In Figure 6, all the disease causing missense mutations are indicated within PH, SH2, and the kinase domains.…”
Section: Structure^function Correlationsmentioning
confidence: 99%
“…Thus, it is not surprising that the known single codon hot spot R520 (Hagemann et al, 1994;Zhu et al, 1994;Conley et al, 1994;Gaspar et al, 1995) was found in our study cohort, in three independent families (families 19-21) with two different missense mutations (R520G and R520Q) ( Table 1). Other arginine-coding CpG dinucleotide was implicated in the recurrent substitution R562W (patient 26), located close to the catalytic site of the protein and interacting with the side chain of the invariant W563 (Hagemann et al, 1994;Conley et al, 1994;Vorechovsky et al, 1995;Holinski-Feder et al, 1998).…”
Section: Resultsmentioning
confidence: 99%